The love interest - Dietrich, Cale (2017)
The agents of the secret spy organization are all teenagers. Caden is a Nice: the boy next door, sculpted to physical perfection. Dylan is a Bad: the brooding, dark-souled guy, and dangerously handsome. The girl they are competing for is important to the organization, and each boy will pursue her. They have to be at the top of their game-- because whoever the girl doesn't choose will die. But things become complicated when Caden finds himself falling in love with Dylan.
Keywords: Identity (Psychology) -- Juvenile fiction; Friendship -- Juvenile fiction; Sexual orientation -- Juvenile fiction; Teenagers -- Juvenile fiction; Gays -- Juvenile fiction; Spies -- Fiction; Identity -- Fiction; Love -- Fiction; Friendship -- Fiction; Sexual orientation -- Fiction; Gays -- Fiction; Romance fiction; Spy fiction; Young adult fiction; Science fiction